(untitled) (Eurasian Journal of Research, Development and Innovation, 2023)
This research article explores the effective strategies for enhancing vocabulary acquisition and their impact on language learners’ overall proficiency. Through a comprehensive literature review and empirical investigations, the study identifies and evaluates various strategies, including explicit instruction, context clues, mnemonics, extensive reading, and digital tools. The findings emphasize the importance of implementing these strategies in language learning contexts to optimize vocabulary development and support learners in their language proficiency journey. Practical recommendations are provided for educators, learners, and language professionals to enhance vocabulary acquisition and promote effective communication skills